Birth, death, and revival of spontaneous emission in a three-atom system - Mährlein, Simon; Götzendörfer, Lukas; Günthner, Kevin; Evers, Jorg; von Zanthier, Joachim (Physical Review Research, 2020)
Three identical two-level atoms in free space prepared in particular entangled single-photon excited states display a "birth," "death," and a nonperiodic "revival" of spontaneous emission in selected directions. Instead of recording the spontaneously emitted photon with a maximum probability at t = 0 as for a single atom, a "birth" manifests itself in an initially zero photon detection probability, increasing thereafter in particular directions. Alternatively, the photon detection probability decreases in particular directions from an initially maximal value to completely disappear ("death") and to reappear again ("revival"). We show how these phenomena can be induced in the fully excited system, by projecting the atomic ensemble into the required entangled single-photon excited state via detection of the first two spontaneously emitted photons. To observe death and revival of spontaneous emission it is necessary to provide both spatial and temporal interference for which a minimum of three atoms is required. Hereby, the third atom, located at a large distance with respect to the other two atoms, can be used to tune the time and direction of the death of the photon. From this manipulation of spontaneous decay at a distance, we anticipate multiple applications, in fundamental science as well as in quantum technologies.
CRIS-Team WoS Importer:2021-01-22

Fading channel estimation for free-space continuous-variable secure quantum communication - Ruppert, Laszlo; Peuntinger, Christian; Heim, Bettina; Günthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique Alexander; Leuchs, Gerd; Filip, Radim; Marquardt, Christoph (New Journal of Physics, 2019)
We investigate estimation of fluctuating channels and its effect on security of continuous-variable quantum key distribution. We propose a novel estimation scheme which is based on the clusterization of the estimated transmittance data. We show that uncertainty about whether the transmittance is fixed or not results in a lower key rate. However, if the total number of measurements is large, one can obtain using our method a key rate similar to the non-fluctuating channel even for highly fluctuating channels. We also verify our theoretical assumptions using experimental data from an atmospheric quantum channel. Our method is therefore promising for secure quantum communication over strongly fluctuating turbulent atmospheric channels.
CRIS-Team WoS Importer:2020-03-06

Free-space propagation of high-dimensional structured optical fields in an urban environment - Lavery, Martin P. J.; Peuntinger, Christian; Günthner, Kevin; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Science Advances, 2017)
Spatially structured optical fields have been used to enhance the functionality of a wide variety of systems that use light for sensing or information transfer. As higher-dimensional modes become a solution of choice in optical systems, it is important to develop channel models that suitably predict the effect of atmospheric turbulence on these modes. We investigate the propagation of a set of orthogonal spatial modes across a free-space channel between two buildings separated by 1.6 km. Given the circular geometry of a common optical lens, the orthogonal mode set we choose to implement is that described by the Laguerre-Gaussian (LG) field equations. Our study focuses on the preservation of phase purity, which is vital for spatial multiplexing and any system requiring full quantum-state tomography. We present experimental data for the modal degradation in a real urban environment and draw a comparison to recognized theoretical predictions of the link. Our findings indicate that adaptations to channel models are required to simulate the effects of atmospheric turbulence placed on high-dimensional structured modes that propagate over a long distance. Our study indicates that with mitigation of vortex splitting, potentially through precorrection techniques, one could overcome the challenges in a real point-to-point free-space channel in an urban environment.
CRIS-Team Scopus Importer:2022-06-05

High-dimensional intracity quantum cryptography with structured photons - Sit, Alicia; Bouchard, Frederic; Fickler, Robert; Gagnon-Bischoff, Jeremie; Larocque, Hugo; Heshami, Khabat; Elser, Dominique; Peuntinger, Christian; Günthner, Kevin; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd; et al. (Optica, 2017)
Quantum key distribution (QKD) promises information-theoretically secure communication and is already on the verge of commercialization. The next step will be to implement high-dimensional protocols in order to improve noise resistance and increase the data rate. Hitherto, no experimental verification of high-dimensional QKD in the single-photon regime has been conducted outside of the laboratory. Here, we report the realization of such a single-photon QKD system in a turbulent free-space link of 0.3 km over the city of Ottawa, taking advantage of both the spin and orbital angular momentum photonic degrees of freedom. This combination of optical angular momenta allows us to create a 4-dimensional quantum state; wherein, using a high-dimensional BB84 protocol, a quantum bit error rate of 11% was attained with a corresponding secret key rate of 0.65 bits per sifted photon. In comparison, an error rate of 5% with a secret key rate of 0.43 bits per sifted photon is achieved for the case of 2-dimensional structured photons. We thus demonstrate that, even through moderate turbulence without active wavefront correction, high-dimensional photon states are advantageous for securely transmitting more information. This opens the way for intracity high-dimensional quantum communications under realistic conditions.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Free-space optical communication; Optical vortices; Quantum cryptography

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Quantum-limited measurements of optical signals from a geostationary satellite - Günthner, Kevin; Khan, Imran; Elser, Dominique Alexander; Stiller, Birgit; Bayraktar, Ömer; Mueller, Christian R.; Saucke, Karen; Troendle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optica, 2017)
The measurement of quantum signals that travel through long distances is fundamentally and technologically interesting. We present quantum-limited coherent measurements of optical signals that are sent from a satellite in geostationary Earth orbit to an optical ground station. We bound the excess noise that the quantum states could have acquired after having propagated 38,600 km through Earth’s gravitational potential, as well as its turbulent atmosphere. Our results indicate that quantum communication is feasible, in principle, in such a scenario, highlighting the possibility of a global quantum key distribution network for secure communication.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (010.1300) Atmospheric propagation; (060.1660) Coherent communications; (060.2605) Free-space optical communication; (270.5565) Quantum communications; (270.5568) Quantum cryptography

Quantum-limited measurements of optical signals from a satellite in geostationary earth orbit - Günthner, Kevin; Khan, Imran; Elser, Dominique; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Quantum-limited measurements of signals from geostationary earth orbit - Elser, Dominique; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (European Conference on Optical Communication, ECOC, 2016)
Quantum key distribution (QKD) has been implemented in metropolitan area networks around the world. Optical satellite communication is seen as suitable to provide the missing long-haul interconnections. We validate this approach by quantum measurements of optical signals from space.
CRIS-Team Scopus Importer:2021-06-29

Quantum measurements of signals from the Alphasat TDP1 laser communication terminal - Elser, D.; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, K.; Tröndle, D.; Heine, F.; Seel, S.; Greulich, P.; Zech, H.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Quantum optics [1] can be harnessed to implement cryptographic protocols that are verifiably immune against any conceivable attack [2]. Even quantum computers, that will break most current public keys [3, 4], cannot harm quantum encryption. Based on these intriguing quantum features, metropolitan quantum networks have been implemented around the world [5-15]. However, the long-haul link between metropolitan networks is currently missing [16]. Existing fiber infrastructure is not suitable for this purpose since classical telecom repeaters cannot relay quantum states [2]. Therefore, optical satellite-to-ground communication [17-22] lends itself to bridge intercontinental distances for quantum communication [23-40].
CRIS-Team Scopus Importer:2021-06-29

QUBE-II - Quantum Key Distribution with a CubeSat - Hutterer, Martin; Auer, Michael; Baliuka, Adomas; Bayraktar, Ömer; Freiwang, Peter; Gall, Marcell; Günthner, Kevin; Haber, Roland; Janusch, Janko; Knips, Lukas; Kobel, Pascal; Krauss, Markus; et al. (IAC-22-B4.9-GTS.5.5,x70823, 2022)
Keywords: QKD; CubeSat; QUBE; Quantum Payload; Quantum Mechanics; QRNG

Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication